Comprehensive analysis of the WRKY gene family in Cucumis metuliferus and their expression profile in response to an early stage of root knot nematode infection - Ling, Jian; Liu, Rui; Hao, Yali; Li, Yan; Ping, Xingxing; Yang, Qihong; Yang, Yuhong; Lu, Xiaofei; Xie, Bingyan; Zhao, Jianlong; Mao, Zhenchuan (Frontiers in Plant Science, 2023)
Root-knot nematode (RKN) is a major factor that limits the growth and productivity of important Cucumis crops, such as cucumber and melon, whick lack RKN-resistance genes in their genome. Cucumis metuliferus is a wild Cucumis species that displays a high degree of RKN-resistance. WRKY transcription factors play important roles in plant response to biotic stresses. However, little is known on the function of WRKY genes in response to RKN infection in Cucumis crops. In this study, Cucumis metuliferus 60 WRKY genes (CmWRKY) were identified in the C. metuliferus genome, and their conserved domains were classified into three main groups based on multiple sequence alignment and phylogenetic analysis. Synteny analysis indicated that the WRKY genes were highly conserved in Cucumis crops. Transcriptome data from of C. metuliferus roots inoculated with RKN revealed that 16 CmWRKY genes showed differential expression, of which 13 genes were upregulated and three genes were downregulated, suggesting that these CmWRKY genes might be important for C. metuliferus response to RKN infection. Two differentially expression CmWRKY genes (CmWRKY10 and CmWRKY28) were selected for further functional analysis. Both CmWRKY genes were localized in nucleus, indicating they may play roles in transcriptional regulation. This study provides a foundation for further research on the function of CmWRKY genes in RKN stress resistance and elucidation of the regulatory mechanism.